Regional precipitation estimations in Central America using the Weather Research and Forecast model - Maldonado, Tito; Alfaro, Eric J.; Amador, Jorge A.; Rutgersson, Anna (Revista de Biología Tropical, 2018)
Abstract: Using the regional climate model WRF, and the NCEP-NCAR Reanalysis Project data as boundary and initial conditions, regional precipitation for Central America was estimated by means of the dynamical downscaling technique for two selected periods: January 2000 and September 2007. Four-nested domains, d01, d02, d03 and d04 with a grid-resolution of 90 km, 30 km, 10 km, and 3.3 km respectively, were configured over this region. The runs were reinitialized every 5 days with 6 h of spin-up time for adjustment of the model. A total of eight experiments (four per month) were tested in order to study: a) two important Cumulus Parameterization Schemes (CPS): Kain-Fritsch (KF) and Grell-Devenyi (GD); and b) the physical interaction between nested domains (one- and two-way nesting), during each simulated month. The modeled precipitation was in agreement with observations for January 2000, and also captured the mean climate features of rainfall concerning magnitude, and spatial distribution, such as the particular precipitation contrast between the Pacific and the Caribbean coast. Outputs of the coarse domains (d01, d02, and d03) for September 2007 revealed differences between experiments within the domains when a visual comparison of the spatial distribution was made. However, for the inner grid (d04), all the experiments, showed a similar spatial distribution and magnitude estimation, mainly in those runs using one-way nesting configuration. The results for the month of September differed substantially with the observations, which could be related to associated deficiencies in the boundary condition that do not reproduce well the transition periods from warm to cold ENSO episodes for the selected periods of study. In all the experiments, the KF scheme calculated more precipitation than the GD scheme and it was associated to the ability of the GD scheme to reproduce spotty but intense rainfall, and apparently, this scheme was reluctant to activate, showing frequent events of low intensity rain. However, when rainfall did develop, it was very intense. Also, the time series did not replicate specific precipitation events. Thus, the 5-days integration period used in this study was not enough to reproduce short-period precipitation events. Finally, physical interaction issues between the nested domains were reflected in discontinuities in the precipitation field, which have been associated with mass field adjustment in the CPS. Rev. Biol. Trop. 66(Suppl. 1): S231-S254. Epub 2018 April 01.